Agricultural Development’s Influence on Rural Poverty Alleviation in the North Buton Regency, Indonesia—The Mediating Role of Farmer Performance - Yohanes Boni (Economies, 2022)
Low productivity and farmer business competitiveness are central issues for agricultural development and rural poverty alleviation. This study aimed to determine the influence of agricultural development on rural poverty alleviation. Data were obtained from farmers’ groups in the North Buton Regency in 2019 using questionnaires and analyzed using AMOS. The results showed that agricultural development improves farm business performance and influences rural poverty alleviation. Farm business performance leads to rural poverty alleviation. The influence of agricultural development on rural poverty alleviation was magnified when supported by improved farm enterprise performance. Therefore, agricultural development is the flagship program for poverty alleviation of rural farmers in the North Buton Regency.